สภาพการอยู่อาศัยในโครงการเช่าพักอาศัยของชาวญี่ปุ่น : กรณีศึกษาสุขุมวิทซอย 41, กรุงเทพมหานคร - สุรวุฒิ วัฒนพรพรหม (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
This research has as its objective to study the social and economic conditions, lifestyle, and living conditions in rental apartments occupied by Japanese residents, as well as problems they experience living there. The Sukhumwit Soi 41 area was chosen for the study as the Japanese like to live in a peaceful environment close to the Japanese community which has public parks and convenient transport. In conducting the research, data was collected from a sample population of 157 people involved with the rental projects according to the Yamane formula by distributing questionnaires and conducting interviews, along with the projects themselves of which the characteristics being surveyed. Research results reflect the future needs for accommodation of the Japanese living in the area. They can also be used as guidelines for improving the existing functional area of the dwellings to really meet the needs of the residents, enhancing Thailand’s reputation in the process. The study of the Japanese residents’ lifestyles found that they generally have a good education with a regular monthly income and most live by themselves. Those of working age live in Thailand for business reasons while those of retirement age choose to live in Thailand as the cost of living here is low, corresponding to their pension. The former group mostly goes out to work during the day while the retired group mostly stays home in their residences.The locations of the projects in the sample area were found to be suitable for the Japanese, but some areas in the rental projects did not meet their needs. As regards living adjustment problems and rental project problems, it was found that the functional area in the apartments was not adequate for the Japanese lifestyle. It is recommended that rental projects should be improved to better suit the Japanese residents, who like to maintain their native cultural lifestyle. Research results also found that the residents like to have a full range of facilities and spend the majority of their time in their apartments. Therefore, improvements should focus on the apartments themselves, including having a Japanese style entrance hall and an open kitchen connecting to the living room to form one room. Moreover, the shower and the bathtub should be in separate areas. Safety concerns for the elderly must also be considered.